ANALISIS KONFLIK TOKOH DALAM NOVEL POSESIF KARYA LUCIA PRIANDARINI - Rismayanti, Syarifah Devi; Martono, Martono; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis paper analyzes how the characters in a novel â€œPosesifâ€ by Lucia Priandarini face both internal and external conflicts that occur and discusses the implementation of the results of research into the curriculum of Indonesian language learning at the second semester of XII senior high school. This study aims to describe (1) internal and external conflicts experienced by the characters in the novel titled â€œPosesifâ€ by Lucia Priandarini, and (2) plans to implement the results of research into Indonesian language learning curricula at the second semester of XII senior high school. This research was conducted in a qualitative form presented descriptively with a behavioristic literature psychology approach. The researcher acted as a key instrument in data collection, with data collection techniques using documentary studies. Based on the results, the internal conflicts of the characters include anxiety, disappointment, anger, regret, sadness, fear, happy, longing, hesitation, amazement, curiosity, shock, wonder, annoyance, suspicion, offence, shame, and aversion. The external conflicts include disagreements, tensions, clashes, debates, and disputes. The results of this study canÂ be used asÂ a reference for teaching materials by Indonesian Language teachers in the second semester of XII senior high school on competencies 3.9 and 4.9.Keywords: Conflicts, Characters, Novel